Chapter Gog and Magog Using Concepts of Apocalyptic Enemies in the Hussite era - Cermanová , Pavlína (De Gruyter, 2016)
This volume addresses Jewish, Christian and Muslim future visions on the end of the world, focusing on the respective allies and antagonists for each religious society. Spanning late Antiquity to the early modern period, the collected papers examine distinctive aspects represented by each religion's approach as well as shared concepts.